An object-oriented graphics interface design and optimization software for cross-sectional shape of automobile body - Zuo, Wenjie (Advances in engineering software (1992), 2013)
•A cross-sectional shape optimization method was proposed to achieve a high stiffness and lightweight thin-walled beam.•Object-oriented programming and design patterns were adopted to design and implement the software framework.•Genetic algorithm solved the nonlinear optimization problem and obtained the optimal section shape.•The cross-sectional area was minimized and the stiffness and manufacturing demands were satisfied. At the conceptual design stage, automobile body is evaluated by simplified frame structure, consisting of thin-walled beams (TWBs). In the automobile practice, design engineers mostly rely on their experience and intuition when making decisions on cross-sectional shape of TWBs. So this paper presents a cross-sectional shape optimization method in order to achieve a high stiffness and lightweight TWB. Firstly, cross-sectional property formulations is summarized and reviewed. Secondly, we build up a shape optimization model to minimize the cross-sectional area and satisfy the stiffness and manufacturing demands. The objective and constraints are nonlinear polynomial functions of the point coordinates defining the cross-sectional shape. Genetic algorithm is introduced to solve this nonlinear optimization problem. Thirdly, object-oriented programming and design patterns are adopted to design and implement the software framework. Lastly, numerical example is used to verify the presented method. This software, “SuperBeam” for short, is released for free and does speed up the conceptual design of automobile body.